Avaliando a diversidade funcional de insetos aquáticos em riachos sob a influência de diferentes usos do solo. - Gimenez, Barbara Carolina Garcia (2014)
The land use is a stressor factor that can change the spatial environmental heterogeneity in streams and this can influence the different ecological attributes of communities. Thus, we tested the hypothesis that the diversity of taxa and functional diversity of aquatic insect communities differ between rural and urban streams. Three facets of functional diversity (functional richness, functional evenness and functional dispersion) were used. In rural streams, the higher structural complexity contributed to the occurrence of sensitive taxa (specialists) that, in general, do not share the categories of functional traits each other, a fact that resulted in high taxonomic and functional diversity in these streams. In contrast, the processes of urbanization and more frequently impacts altered most drastically the abiotic limnological variables and led to a simplification of habitats in urban streams, facilitating the predominance of tolerant taxa (generalists), which in turn tend to share a larger number of traits, reducing the taxonomic and functional diversity at these sites. Therefore, to evaluate the functional diversity of aquatic insects under the influence of different land use is essential for a better understanding of the functioning of this community in face of increasingly larger and more frequent changes which are subject lotic ecosystems.